Pursuing behavioral realism in Virtual Reality for fire evacuation research. (8th October 2020) - Arias, Silvia; Wahlqvist, Jonathan; Nilsson, Daniel; Ronchi, Enrico; Frantzich, Håkan
Summary: The use of virtual reality in human behavior in fire research has the advantage of being able to produce results comparable to more traditional laboratory or field experiments. This method relies not only on the technology employed but also on the participants' perception of realism when exposed to a virtual emergency scenario. A virtual scenario can be perceived as realistic based on the way it looks and on the way objects in it operates. However, in some experiments, behavioral realism can be the most relevant feature to obtain meaningful results. In this article, knowledge gained by running four different virtual reality experiments is presented in the form of challenges and recommendations to enhance the realism of the virtual experience. Although not in a comprehensive way, these challenges and recommendations refer to different parts of the process of running a virtual reality experiment for research in human behavior in fire, from the design of the environment to the behavior of the participants in it. The recommendations provided are based on observations. By spreading this knowledge, it is expected to aid the broader fire safety engineering community to develop more realistic virtual reality experiments for data collection on human behavior in fire.